Genetic influence is linked to cortical morphology in category-selective areas of visual cortex - Nooshin Abbasi; John Duncan; Reza Rajimehr (Nature Communications, 2020)
It remains unclear whether the functional organization of the visual cortex is shaped by genetic or environmental factors. Using fMRI in twins (n = 424), these authors show that activation patterns in category-selective areas are heritable, and that the genetic effects in these areas are linked to structural properties of cortical tissue.